The role of Armenia's foreign trade and development opportunities in the context of cooperation with Global South countries - Meruzhan Markosyan; Elyanora Matevosyan; Ashot Markosyan (OrdnungsPolitisches Portal (OPO), 2025)
Foreign trade plays a central role in Armenia's economic development, shaping GDP through both internal and external factors. In small and open economies such as Armenia, external trade and integration strategies are decisive for growth. The state budget data for 2022-2024 underline this dependence: VAT revenues from imports formed 65.2% in 2022, 67.4% in 2023, and 57.5% in 2024, while excise taxes from imports accounted for 61.0%, 76%, and 60% respectively. These figures demonstrate that Armenia's fiscal stability is largely driven by foreign trade flows. Between 2019 and 2024, Armenia's trade structure shifted notably, with the share of "other countries" (primarily Global South states) rising from 39% to 53.8%. This trend reflects diversification, new markets, and more efficient partnerships. For Global South countries, international trade integration provides access to growth, technology transfer, and investment inflows, making foreign trade a cornerstone of their development path. For Armenia, improving the export structure, fostering high value-added production, and reducing reliance on raw materials are critical. Strengthening competitiveness, enhancing the investment climate, and adopting international best practices are equally important. This study therefore analyzes Armenia's foreign trade dynamics during 2021-2024 and outlines strategic directions for inclusive growth, regional integration, and cooperation within the Global South.
Keywords: 330; Global South; foreign trade strategy; economic diversification; competitiveness; economic integration; international trade; developing countries; export promotion; economic stability